151 Cardiac Myosin-Binding Protein C is a Novel Marker of Myocardial Injury and Fibrosis in Patients with Aortic Stenosis. (3rd June 2016) - Anand, Atul; Chin, Calvin; Shah, Anoop; Kwieciński, Jacek; Vesey, Alex; Cowell, Joanna; Weber, Ekkehard; Kaier, Thomas; Newby, David; Dweck, Marc; Marber, Michael; Mills, Nicholas
Abstract : Background: Cardiac myosin binding protein C (cMyC) is an abundant sarcomeric protein and a novel highly specific marker of myocardial injury. Given myocyte death characterises the transition from hypertrophy to replacement myocardial fibrosis in advanced aortic stenosis, we hypothesised that serum cMyC concentrations would be associated with cardiac structure and outcomes in patients with aortic stenosis. Methods: cMyC was measured in two cohorts: a mechanism cohort of patients with aortic stenosis (n = 161) and healthy controls (n = 46) who underwent cardiac magnetic resonance imaging, and an outcomes cohort with aortic stenosis (n = 104) followed for a median of 11.3 years. Tru cut myocardial biopsies were obtained from 10 patients in the mechanism cohort who underwent aortic valve replacement. These samples underwent staining and analysis for myocyte death. Results: In the mechanism cohort, cMyC concentration correlated with left ventricular mass (r = 0.59, 95% CI 0.47–0.68, p < 0.0001), fibrosis volume (r = 0.57, 95% CI 0.45–0.67, p < 0.0001) and extracellular volume (r = 0.28, 95% CI 0.12–0.42, p = 0.0004) in patients with aortic stenosis but not in controls (Figure 1). In those with late gadolinium enhancement (LGE), cMyC was higher (32 [21–56] ng/L vs 17 [12–24] ng/L without LGE, p < 0.001). cMyC was unrelated to aortic transvalvular gradient or objective assessment of coronary disease. Unadjusted Cox proportional hazards analysis in the outcomes cohort showed greater all-cause mortality (HR 1.53 per doubling of cMyC, 95% CI 1.13–2.06, p = 0.006). In exploratory analyses, a relationship was observed between cMyC and the rate of myocyte death (expressed as the sum of apoptosis, oncosis and autophagy counts) in biopsy samples (r = 0.67, 95% CI 0.08–0.92, p = 0.03). Clear differences were observed in staining patterns for oncosis and autophagy between subjects with low and high cMyC concentrations (Figure 2). Conclusion: Serum cMyC concentration is associated with myocardial hypertrophy, fibrosis and an increased risk of mortality in aortic stenosis. The quantification of serum sarcomeric protein concentrations have major potential to provide objective measures of disease progression and to guide clinical decisions in patients with aortic stenosis.